Respuesta :
Answer:
[tex]x=1[/tex]
Step-by-step explanation:
[tex]1+(3x-3)=1[/tex]
First, you have to take the one that is outside of the Parenthesis and take it to the other side. That would mean it would be this:
[tex]3x-3=1-1[/tex]
1 - 1 is 0
[tex]3x-3=0\\[/tex]
Move the -3 to the other side, which makes it positive;
[tex]3x=3[/tex]
Divide both sides by 3
[tex]x=1[/tex]
If you want to check it, you can replace 1 in the original equation:
[tex]1+(3X1-3)=1[/tex]
[tex]1+(0)=1[/tex]
[tex]1=1[/tex]
So x=1